Methionine salvage and S-adenosylmethionine: essential links between sulfur, ethylene and polyamine biosynthesis - Sauter, Margret; Hell, Rüdiger; Wirtz, Markus (Biochemical journal, 2013)
Both Met (methionine) and SAM (S-adenosylmethionine), the activated form of Met, participate in a number of essential metabolic pathways in plants. The subcellular compartmentalization of Met fluxes will be discussed in the present review with respect to regulation and communication with the sulfur assimilation pathway, the network of the aspartate-derived amino acids and the demand for production of SAM. SAM enters the ethylene, nicotianamine and polyamine biosynthetic pathways and provides the methyl group for the majority of methylation reactions required for plant growth and development. The multiple essential roles of SAM require regulation of its synthesis, recycling and distribution to sustain these different pathways. A particular focus of the present review will be on the function of recently identified genes of the Met salvage cycle or Yang cycle and the importance of the Met salvage cycle in the metabolism of MTA (5′-methylthioadenosine). MTA has the potential for product inhibition of ethylene, nicotianamine and polyamine biosynthesis which provides an additional link between these pathways. Interestingly, regulation of Met cycle genes was found to differ between plant species as shown for Arabidopsis thaliana and Oryza sativa.
Gesehen am 11.05.2017